High-Performance Work Practices and Organizational Creativity During Organizational Change: A Collective Learning Perspective - Jeong, Inseong; Shin, Shung Jae (Journal of management, 2019)
Drawing on a collective learning perspective, we theorized and tested how and when high-performance work practices are likely to enhance organizational creativity. Using a sample of 454 Korean companies across 16 industries in manufacturing, service, and banking areas, with time-lagged and multisource data, we found that high-performance work practices led to more organizational creativity when the companies underwent organizational change. We also found that the employees’ collective learning mediated the interaction effect of high-performance work practices and organizational change on organizational creativity. We discuss the theoretical and practical implications of these findings.